The Emergence of Psychoanalytic Metaneuropsychology: A Neuropsychoanalytically Informed Reconsideration of Early Psychic Development - Mellor, Matthew John (Frontiers in Psychology, 2021)
This paper is principally concerned with reappraising some of the major disagreements that separated the Viennese and the Kleinians during the British Psychoanalytical Society’s Controversial Discussions. Of particular focus are questions pertaining to the genesis of ego development, the beginnings of object-relating, and the role of unconscious phantasy in respect of these phenomena. The aim of the investigation is to inquire into the light that may be shed on the once intractable conflicts surrounding these questions by bringing to bear more recent developments from psychoanalysis and the neurosciences. First, various key issues from the Controversial Discussions are outlined, before the paper turns to work by Jaak Panksepp and Mark Solms that bears on these older arguments and the Freudian theories that underpinned them. With these conceptual foundations established, three questions are posed and discussed with a view to understanding the implications of recent neuropsychoanalytic thinking for some of the entrenched conflicts that divided the British Society. These questions include: (1) what does it mean for the ego if the id is conscious? (2) What does recent neuroscientific knowledge tell us about whether the ego should be thought of as present from birth? (3) How can we understand and locate unconscious phantasy if the main part of the mind that Freud thought of as unconscious is not so? Research from the arena of infant development – particularly the material and analysis of infant observation – is drawn on to illustrate various conclusions. The paper ultimately concludes that taking such an interdisciplinary approach can reveal renewed justification for aspects of the Kleinian metapsychology.